Interaction of the 2,4-dichlorophenoxyacetic acid herbicide with soil organic matter moieties: a theoretical study - Aquino, A.J.A; Tunega, D; Haberhauer, G; Gerzabek, M.H; Lischka, H (European journal of soil science, 2007)
The determination of the structure of humic substances from soils and natural waters is an intriguing problem in soil science. Humic substances consist of molecules covering a broad distribution of molecular size and involving different functional groups. Taking this into account, we have chosen smaller model systems with functional groups typically present in humic substances. We investigated theoretically, by quantum chemical calculations, the environmental effects on the complexes formed from the interaction of 2,4-dichlorophenoxyacetic acid and its anion with acetaldehyde, methanol, methylamine, protonated methylamine, acetic acid and water. The important case of a cation bridge mechanism, with Ca²⁺ as the bridging cation, is also included into the set of model reactions. It is found that this cation bridge belongs to one of the most stable mechanisms of fixation of organic compounds in soils. According to our calculations the hydroxyl group forms the most stable complexes with 2,4-D in a polar solvent environment.